Application of Check-All-That-Apply (CATA) for formulating and characterizing sargassum seaweed-based kombucha drink: Effects of different sugar types and fermentation times - Isnaini Cahyuning; Nurdiana Risma Safita; Hardiningtyas Safrina Dyah; Kunicki Anya; Corcoran Ashley; Ramadhan Wahyu (BIO Web of Conferences)
One approach to refining the taste of Sargassum tea involves subjecting it to fermentation to produce Kombucha tea. This study was designed to assess the impact of fermentation duration and various types of sugars on the sensory attributes of Seaweed Kombucha, alongside the physicochemical properties and flavor profile associated with the optimal sugar type and a fermentation duration. Seaweed Kombucha samples were subjected to treatments involving different sugars (sucrose, sorbitol, and steviol) and fermentation duration of 9 days, with sampling intervals at days 0, 3, 5, 7, and 9. The characteristics of Seaweed Kombucha were evaluated based on parameters such as pH, alcohol content, color, total sugar content, and sensory analysis. Utilizing hedonic sensory assessment, the most favorable Seaweed Kombucha sample was identified as the one treated with steviol sugar and fermented for 3 days. The sensory flavor profile of Seaweed Kombucha was elucidated through Check-All-That-Apply (CATA) and Gas Chromatography-Mass Spectrometry (GC-MS) methodologies. The optimal Seaweed Kombucha sample exhibited a volatile compound profile comprising acids, alcohols, ketones, heterocyclic compounds, and other constituents.